ANALYSIS OF TRANSLATION METHODS USED IN ENGLISH IDIOM TRANSLATIONS INTO INDONESIAN IN INSTAGRAM CAPTIONS OF CRISTIANO RONALDO - Sari, Wati Purnama (UG Journal, 2021)
This research aims at (1) finding out the types of English idioms in Christiano Ronaldo’s Instagram Captions, (2) finding out the most employed translation method in translating English idioms into its Indonesian translation using Newmark’s translation methods theory. This research is a type of qualitative research, because the researcher uses the textual data. The results of the research are from 25 data analyzed, the English idioms existed in Christiano Ronaldo’s Instagram captions are Fixed statement (16 data), Cliché (7 data), and Proverb (2 data). The translation method used are Communicative translation (14 data), Literal translation (8 data), and Word-for-word translation (3 data). There are 3 types of English idioms appeared in Christiano Ronaldo’s Instagram captions namely, Fixed statements, Cliché, and Proverb. Then, the most translation method used for translating those idioms is Communicative translation method. Through this research results we can see that in translating English idioms, the feature of “see translation” in Instagram captions uses Communicative translation method. It is used in order to have an adequate understanding and readable translation for the Instagram users about the English idioms’ meaning of SL to TL. So, Instagram users in TL can understand the information of SL better.